Metal-Free Synthesis of 2-Benzylideneindolin-3-ones via a Nucleophilic/Rearrangement/Azide–Alkene Cascade Reaction - Tang, Quan; Huang, Sheng-Chao; Wang, Hua; Long, Tianyu; Kong, Han-Han; Yang, Qing-Qing; Huang, Nianyu; Wang, Long (Synlett, 2024)
A metal-free synthesis of 2-benzylideneindolin-3-ones through a formal [4+1] annulation from o-azidobenzaldehydes and terminal alkynes has been developed. The method features operational simplicity, mild reaction conditions, and ready availability of starting materials. A broad range of 2-benzylideneindolin-3-ones were prepared in moderate to excellent yields. Mechanistic studies indicated that the reaction might proceed through a nucleophilic addition/rearrangement/azide–alkene cycloaddition pathway to produce 2-benzylideneindolin-3-ones.
Keywords: metal-free synthesis; benzylideneindolinones; azidobenzaldehydes; terminal alkynes; azide–alkene cycloaddition; cascade reaction